Seabather's eruption: report of case in northeast region of Brazil Prurido do traje do banho: relato de caso na região nordeste do Brasil - André Luiz Rossetto; Luís Antônio de Oliveira Proença (Sociedade Brasileira de Dermatologia, 2012)
Seabather's eruption is characterized by the occurrence of intensely itchy erythematous papules observed mainly in the region covered by swimwear. The dermatitis occurs due to the contact of planula larvae of scyphomedusae Linuche unguiculata with the skin. The swimsuit pressure triggers the action of the poisonous stinging structures carried by the larvae. The case described occurred in a child who, while bathing in the ocean waters of the Northeast coast of Bessa's Beach located in the city of Joao Pessoa, state of Paraiba, showed typical clinical signs of the disease. It was concluded that the report of the case showed clinical and therapeutic implications for doctors working in all of the Brazilian coastal areas. O prurido do traje de banho é uma erupção caracterizada por pápulas eritematosas, intensamente pruriginosas, localizadas principalmente sob os trajes dos banhistas de mar. A dermatite ocorre pelo contato com as larvas plânulas da cifomedusa Linuche unguiculata que disparam seus nematocistos na pele do acidentado a partir das suas células de defesa, os cnidócitos. O caso ocorreu em uma criança que ao se banhar nas águas oceânicas do litoral da Região Nordeste na Praia do Bessa localizada na cidade de João Pessoa, Estado da Paraíba, apresentou quadro clínico típico da enfermidade. Concluiu-se que o relato do caso evidenciou implicações clínicas e terapêuticas para os médicos que atuam em todas as áreas litorâneas brasileiras.